RESPON PARA PENEGAK HUKUM TERHADAP PELAKU PERAMBAHAN HUTAN KONSERVASI ALAM LOK PAHAR DI KABUPATEN MANGGARAI TIMUR - Rola, Yustina; Pello, Jimmy; Medan, Karolus Kopong (Petitum Law Journal, 2023)
Constitution Number 18 of 2013 concerning Prevention And eradication destruction Affirmed forest in Article 3 and Act Number 41 of 1999 concerning Deep forestry Article 50 paragraph 3 letter (b) and Article 78 paragraph 2 which is Wrong One threatened act criminal However Constitution This has revoked and changed with Act Number 18 of 2013. Objective Research 1. Explain background factors public in the district manggarai east do action encroachment forest conservation natural lock thigh ; 2, explained about PPNS response to perpetrator encroachment forest conservation natural lock fee in the district manggarai east. Which factor background happening encroachment forest conserve natural lock understand is income from activity particular , education (knowledge about law ), weakness guard forest And lightness law (control law), many request will wood . Response from PPNS against affluent society results forest on forest conservation natural based on results study to PPNS performance yet effective Because Not yet There is response Serious from PPNS regarding area growing forest bad. Conclusion from study This is underlying factors happening action browsing forest conservation natural that is income from activity particular, education (knowledge about law), weakness guard forest And lightness law (control law), many request will wood. Response from PPNS against affluent society results forest on forest conservation natural based on results study to PPNS performance yet effective Because Not yet There is response Serious from PPNS regarding area growing forest bad. Advice given writer is should minimize existing encroachment, control from government district, BBKSDA NTT, more often supervise forest conservation natural Lok Pahar, preferably government local more often stage socialization about necessity guard existing forest.